2019
DOI: 10.1038/s41598-019-51727-3
|View full text |Cite
|
Sign up to set email alerts
|

Diverging roles of the anterior insula in trauma-exposed individuals vulnerable or resilient to posttraumatic stress disorder

Abstract: Distinct brain alterations in response to traumatic events may render trauma-exposed individuals either resilient or vulnerable to posttraumatic stress disorder (PTSD). This study compared regional cerebral metabolic rate of glucose (rCMRglu) among trauma-exposed individuals with current PTSD (PTSD group, n = 61), those without current PTSD (Resilience/Recovery group, n = 26), and trauma-unexposed controls (Control group, n = 54). All participants underwent brain [18F]-fluorodeoxyglucose positron emission tomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
1
7
1
Order By: Relevance
“…However, attention/executive deficit with prefrontal hypometabolism was persisting in all patients 6 months after COVD-19 onset. Lasting anxio-depressive symptoms were also observed in agreement with persistent hypometabolism in the right insula which is involved in post-traumatic stress disorder [10]. Our data also reveals heterogeneity in patient outcomes.…”
Section: Suv Ratiosupporting
confidence: 79%
“…However, attention/executive deficit with prefrontal hypometabolism was persisting in all patients 6 months after COVD-19 onset. Lasting anxio-depressive symptoms were also observed in agreement with persistent hypometabolism in the right insula which is involved in post-traumatic stress disorder [10]. Our data also reveals heterogeneity in patient outcomes.…”
Section: Suv Ratiosupporting
confidence: 79%
“…Nonetheless, results from human studies and extensive inter-connectivity of the insular cortex with other fear and anxiety processing brain regions make it worth extensive investigation. Several human neuroimaging studies have consistently shown that the altered structure and activity of the insular cortex is related to anxiety disorders 5 7 . Additionally, the insular cortex has widespread mutual connections with cognitive and emotional information processing brain regions 8 , 9 , therefore, it is well positioned to integrate and assess various information.…”
Section: Introductionmentioning
confidence: 99%
“…There were several reports regarding stress with brain glucose metabolism of amygdala, insula, striatum (54; 55) and depression with that of hippocampus, frontal lobe (56). The association of psychological cluster with brain glucose metabolism of thalamus and hippocampus became prominent in 5-year follow-up, not in baseline study.…”
Section: Discussionmentioning
confidence: 99%